Parental Knowledge of Breastfeeding and Nutrition: Influence on Oral Health and Self-Reported Early Childhood Caries in Preschool Children in Croatia - Marija Badrov; Marija Matijević; Antonija Tadin (Pediatric Reports)
Aim: Parents’ knowledge of oral health plays a key role in shaping their children’s habits and preventing early childhood caries, particularly through breastfeeding and nutrition. This study aimed to assess parents’ knowledge of how dietary habits affect both oral health and early childhood caries rates. Materials and methods: An online cross-sectional survey was conducted among 595 parents of children aged 3 to 6 years old using a self-structured questionnaire. Sociodemographic data, the children’s characteristics, breastfeeding practices, daily diet, the perceived effects of diet on orofacial health, and self-reported dental caries were recorded. The data were analyzed using descriptive statistics, chi-square tests, and regression models. Results: One-third of the children had dental caries (200/595). The prevalence of caries was significantly higher among children from rural areas (40.5%) compared to those from urban areas (31.1%) (p = 0.021) and in low-income families (72.7%) compared to middle-income (35.4%) and high-income (25.1%) families (p = 0.002). Breastfeeding duration, bottle feeding, and night feeding were not significantly associated with the occurrence of caries. Only 11.1% of parents recognized the role of extended breastfeeding on a child’s demand over one year in promoting the development of tooth decay. Better knowledge was observed among parents with university degrees, in healthcare workers, and in parents with lower incomes (p < 0.05). Conclusions: Dental caries was prevalent, especially among children from rural areas and low-income families. Although there is no direct correlation between the duration of breastfeeding and dental caries, parental awareness of the preventive benefits of breastfeeding remains low. Education for parents about breastfeeding and nutrition’s impact on oral health can have a substantial effect on preventing ECC. Educational efforts aimed at specific audiences are necessary to boost knowledge and advance preventive strategies. This study must recognize its limitations due to its dependence on self-reported caries data. Subsequent research must include clinical dental evaluations to achieve findings that are both dependable and factual.